HEPATOPATHY INFLUENCE ON COGNITIVE FUNCTIONS AND PSYCHOEMOTIONAL STATE OF PATIENTS IS ANALYSED - Gumeniuk, L.I.; Gubska, O.Ju. (The Ukrainian Scientific Medical Youth Journal, 2017)
Benchmarking study of Cognitive function and psychoemotional state of 30 hepatopathy patients was conducted in this article 41,67% of the above-mentioned patients had class C cirrhosis of the liver; 29,17 % of them had chronic hepatitis with cytolytic symptom and cholestasis altogether 20,83% had chronic hepatitis with moderate cytolytic symptom and 8,33% had cytolytic hepatitis with significant cytolytic symptom. From the results it is concluded that higher percent (20,83%) of the patients with class C cirrhosis of the liver suffer from fourth extent of disease hepatic encephalopathy and significant fourth extent of depressive disorder. Patients with chronic hepatitis with moderate cytolytic symptom and chronic hepatitis with cytolytic symptom and cholestasis altogether (4,17% each) suffer to a smaller extent from second or third extent of disease hepatic encephalopathy and first-second and third extent of depressive disorder.